Impact factor of bureaucracy to the tax system - Challoumis Constantinos (Ekonomski Signali, 2023)
This paper is about the sensibility of taxation in the bureaucracy. Therefore, this study is for the impact factor of the tax revenues of the countries which are tax havens subject to the trustworthiness of the tax system. From the view of how much is affected a company that participates in controlled transactions, can obtain the impact of bureaucracy, when there is not that factor with the case that exists in the analysis of transfer pricing. The method of analysis of the impact of bureaucracy in combination with the impact factor of tax revenues is the Q.E. method. It determined the behavior of the tax system subject to bureaucracy.